Drug–drug interactions between epidermal growth factor receptor tyrosine kinase inhibitors and rivaroxaban in vitro and in vivo - Dongxu Wang; Shuanghu Wang; Hualan Wu; Peiwu Geng; Yang An; Xiaoyue Zhou; Minghui Du; Yuwei Li; Jia Chong; Yingying Li; Fang Wang; Zebei Lu; et al. (PLoS ONE, 2025)
Background Tyrosine kinase inhibitor (TKI) and rivaroxaban co-administration is common for patients with cancer and venous thromboembolism. However, the drug–drug interactions (DDIs) between epidermal growth factor receptor (EGFR) TKIs and rivaroxaban remain uncertain. Methods DDIs were investigated in vitro and in vivo. In vitro experiments were conducted using rat liver microsomes, and rivaroxaban metabolites were tested to identify the two TKIs that exhibit the most significant DDIs. The type of inhibition was investigated using Lineweaver-Burk plots. For in vivo experiments, eighteen rats were randomly divided into three groups and pretreated with CMC-Na together with avitinib or gefitinib, or with CMC-Na alone for 7 days. On day 8, rivaroxaban was orally administered to each group. Blood samples were collected at various time points, and plasma rivaroxaban was quantified. Molecular docking was performed to explore the mechanism of DDIs. Results Avitinib and gefitinib showed the most potent inhibitory effects among multiple EGFR TKIs and inhibited rivaroxaban metabolism in a mixed model of noncompetitive and uncompetitive inhibition. The area under the drug-time curve and maximum plasma concentration of rivaroxaban were significantly higher following avitinib and gefitinib pretreatment, while the apparent volume of distribution and clearance rates were significantly lower. Our molecular docking analysis revealed that these two drugs may inhibit rivaroxaban metabolism by overlapping with its binding site on CYP3A4 and CYP2D6. Conclusion These findings confirm the presence of DDIs between EGFR TKIs and rivaroxaban. Avitinib and gefitinib significantly inhibit rivaroxaban metabolism, and their co-administration may aggravate the risk of bleeding.